Psychometric analysis of the state metacognitive inventory in children of 4th and 5th elementary school from Colombia - Arias Gallegos, Walter L. (2022)
In the present study it was analyzed the psychometric properties of the State Metacognitive Inventory (O’Neil & Abedi, 1996) in a sample of elementary school Colombian students, with the aim of facilitate its application in the educational context of Colombia. This is an instrumental study and associative kind. A sample of 220 students was intentionally selected from an educative institution from Barranquilla, 50.5% were women with an average age of 10 years old. It was applied the Vallejos et al.’s (2012) version of the instrument that has a three factor structure: self-knowledge, self-regulation and monitoring. Fort the validity estimation it was applied the confirmatory factor analysis, and for the calculation of reliability, McDonald’s Omega Test was used. The results verified the three factors structure, although only the dimension of self-knowledge obtained adequate reliability indexes. Moreover, by comparison of the self-knowledge levels considering the sex of the students, women had higher punctuations with significant statistics differences.